FORMULASI DAN UJI EFEKTIVITAS GEL DAN SALEP MINYAK KEMANGI (Ocimum basilicum Linn) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Ririn, Ririn; Zulkarnain, Iskandar; Natsir, Siska (Jurnal Ilmiah As-Syifaa, 2016)
Basil is one of a plant that has antibacterial activity on Staphylococcus aureus, the cause of furuncle. To cure the desease it is require preparations with a good penetrability, i.e gels and ointments. The goal of the research was to obtained the most stable both gel and ointment formulations of basil seed oil (Ocimum basilicum Linn.) pharmaceutically and effective microbiologically. Physical stability evaluations were performed by the parameters were organoleptic, viscosity measurement, homogeneity, spreadability, and flowing type at 5oC and 35oC for 12 hours on each temperature for 10 cycles. Organoleptic assay showed that there was no change in color, odor and concistency of all formula. Based on statistic analyses by Randomized design exhibited a significant change of gel and ointment formulation during storage. Homogeneity test showed that all formula possess even particle distribution. Based on rheogram exhibited thixotrophy-plastic flow type. Microbiological assay carried out by observe the formed inhibitory zone. Physical evaluation obtained formula II of gel was the most stable (12% basil seed oil) and formula III of ointment (18% basil seed oil) and microbiologically effective was formula III.Â  While the most effective microbiologically in inhibit the growth of Staphylococcus aureus was gel preparation in 18% concentration of basil seed oil.